A Glucose‐Responsive Polymer Nanocarrier Based on Sulfonated Resorcinarene for Controlled Insulin Delivery. Issue 10 (7th October 2019) - Sergeeva, Tatiana Yu.; Mukhitova, Rezeda K.; Nizameev, Irek R.; Kadirov, Marsil K.; Sapunova, Anastasia S.; Voloshina, Alexandra D.; Mukhametzyanov, Timur A.; Ziganshina, Albina Y.; Antipin, Igor S.
Abstract: A nanocarrier (p(6SRA‐5B)) for glucose‐controlled insulin delivery consists of sulfonated resorcinarenes (SRA) that are assembled into a spherical shell and are attached to each other with phenylboronate linkers. p(6SRA‐5B) is stable in water and blood plasma at normal glucose concentrations. At high glucose levels (>5 mM), p(6SRA‐5B) dissociates into SRA and phenylboronates through competitive interaction with excess glucose. Insulin was successfully encapsulated into the cavity of p(6SRA‐5B) and its release was investigated in water and blood plasma by NMR, UV, CD, and fluorescence spectroscopy. The results show that the dissociation of the nanocarrier and the insulin release occurs with an increase in glucose concentration. At 5 mM glucose, the nanocarrier is stable, and the insulin release does not exceed 10 %. Increasing the glucose concentration to 7.5–10 mM results in a 40–100 % insulin release. p(6SRA‐5B) is thus a promising insulin nanocarrier for the treatment of type 1 diabetes. Abstract : Sweet release : An insulin nanocarrier was synthesized by the microemulsion polymerization of sulfonated resorcinarenes with phenylboronic acid. The nanocarrier is stable at normal glucose levels, and it dissociates at a glucose concentration about 10 mM. The insulin encapsulation and release were investigated by NMR, UV, and fluorescence spectroscopy. An increase in glucose concentration from 5 to 10 mM leads to an increase in the insulin release from 10 to 100 %.